2019
DOI: 10.1021/acs.energyfuels.9b01827
|View full text |Cite
|
Sign up to set email alerts
|

Precise Wettability Characterization of Carbonate Rocks To Evaluate Oil Recovery Using Surfactant-Based Nanofluids

Abstract: Free energy of nanoparticles can increase the surface activity at the solid/oil/liquid contact line and remove oil through the disjoining pressure gradient mechanism. Surfactants can also remove oil mainly by reducing interfacial tension, although raising economic concerns as a result of their adsorption on the rock surface. Introduction of nanoparticles to surfactant solutions seemed to be more prominent in improving the wettability than reducing the interfacial tension, which could offer an opportunity to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…136,140,142 For example, an increased concentration of silica nanoparticles (from 0 to 0.8 wt %) improved the wettability modification effect. 148 However, Al-Anssari et al found that after concentration reached a threshold value, this positive influence became insignificant. They suggested controlling the nanofluid concentration at the corresponding threshold value from an economic perspective.…”
Section: Nanofluid Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…136,140,142 For example, an increased concentration of silica nanoparticles (from 0 to 0.8 wt %) improved the wettability modification effect. 148 However, Al-Anssari et al found that after concentration reached a threshold value, this positive influence became insignificant. They suggested controlling the nanofluid concentration at the corresponding threshold value from an economic perspective.…”
Section: Nanofluid Preparationmentioning
confidence: 99%
“…Increased nanoparticle concentration has a positive influence on wettability alteration toward water-wet conditions. ,, For example, an increased concentration of silica nanoparticles (from 0 to 0.8 wt %) improved the wettability modification effect . However, Al-Anssari et al found that after concentration reached a threshold value, this positive influence became insignificant.…”
Section: Wettability Modifiersmentioning
confidence: 99%
“…Through multiple mechanisms such as ion exchange and double layer expansion (a mechanism which arises when charged solids are immersed in similarly charged fluids, creating a double layer and leading to electrostatic repulsion), low salinity brine promotes the growth of thin water wetting films, reducing the work of adhesion needed to disrupt oil/rock interfaces [52]. Likewise, injecting dispersions of silicon dioxide nanoparticles into the reservoir can penetrate oil/rock interfaces by forming a wedge film [9,29,56]. By doing so, fluids containing nanoparticles will advance over the area previously occupied by the oil phase, reducing the work of adhesion to gradually change the system to a less oil-wet state.…”
Section: Relationship Between Adhesion Force Work Of Adhesion and Wettabilitymentioning
confidence: 99%
“…Of these techniques, contact angle measurement is the most common because such measurements can easily be done under reservoir thermodynamic and fluid conditions; it is less time-consuming; and it can be used to probe specific mineralogical effects on wettability. Contact angles were measured using the sessile drop technique and the modified sessile drop technique until the dual-drop-dual-crystal (DDDC) technique [9] was developed. The DDDC approach helped overcome the deficiencies in the earlier methods in terms of honoring three-phase boundary, obtaining reproducible results, and requiring less aging time.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al, Cheraghian et al, Haeri et al, Songolzadeh and Moghadasi, Zhao et al, and Zhong et al. have shown that the combinations of silica nanoparticles with different surfactants have a good potential to alter wettability from oil-wet to water-wet. Suleimanov et al showed that nonferrous metal NPs can reduce IFT/surface tension . Mohajeri et al, by combining ZrO 2 NPs with sodium dodecyl sulfate and CTAB, showed that the nanofluids optimize IFT/surface tension and alter wettability …”
Section: Introductionmentioning
confidence: 99%